Optimization of physicochemical changes of palm olein with phytochemical antioxidants during deep‐fat frying - Jaswir, Irwandi; Che Man, Yaakob; Kitts, David D. (Wiley, 2000)
Response surface methodology (RSM) was used to optimize the amounts of rosemary and sage extracts together with citric acid as synergist antioxidants in stabilizing refined, bleached, and deodorized palm olein during repeated deep-fat frying of potato chips. For all physicochemical properties studied, these phytochemical antioxidant treatments significantly (P<0.05) reduced the oxidation rate of the oil. During 5 d of frying, anisidine value, peroxide value, free fatty acid, polymer content, color units, viscosity, and absorbances at 232 and 268 nm gradually increased, whereas iodine value and ratio of 18:2/16:0 decreased. Further statistical analyses, including coefficient of determination (R2) and probability of F values, indicated that mathematical models for each physicochemical parameter could be developed confidently in this study, with R2 for all parameters greater than 0.90. These results suggested that an optimal mixture of phytochemical antioxidants derived from rosemary and sage together with citric acid could be produced using RSM for stabilizing thermally processed oil. For many physicochemical parameters examined, the use of moderate levels of antioxidants could result in optimal responses.